The EFFECT OF TWITTER AUTOBASE @ENGLISHFESS TO THE STUDENTS’ ABILITY IN WRITING PROCEDURE TEXT - Siregar, Miftahul Isnaini; , Nurlaili (Journal of English Language and Literature Teaching, 2023)
The objective of the research was to determine whether there was a significant effect of the use of Twitter Autobase @Englishfess to the students’ ability in writing procedure text. This type of research is quantitative research and was conducted using two classes as research samples, namely class X-D as the experimental class consisting of 35 students and class X-C as the control class consisting of 35 students. In the data collection technique, the researcher conducted a pre-test, treatment and post-test by giving a test in the form of an example of a procedure text. The results of this study indicate that there is a significant effect of using Twitter Autobase @Englishfess to the students’ ability in writing procedure text. This can be seen after the data was analyzed, the mean of the experimental group was 74, 45. Meanwhile the mean of the control group is 64, 28. This means that the tenth grade students of SMA Negeri 2 Lubuk Pakam apply Twitter Autobase @Englishfess in learning procedure texts higher than those without Twitter Autobase @Englishfess. After testing the research hypothesis, it turns out that the hypothesis is accepted.